When an Eastern-European Problem Becomes a Pan-European One: The Metaphorical Construction of Europe’s 2022 Energy Crisis - Rositsa Ishpekova; Kalina Ishpekova-Bratanova (Slavia Meridionalis, 2025)
The paper analyses The Economist’s narrative of the 2022 energy crisis in Europe. Conducted within the theoretical framework of Critical Metaphor Analysis (CMA), the analysis establishes that The Economist constructs the EU’s image through a DISEASE-centred metaphoric scenario. The EU is represented as ILL, SUFFERING FROM A DISEASE, SUFFERING NEGATIVE EFFECTS OF A DISEASE, and REQUIRING TREATMENT. Hence three elements of the metaphorical scenario are identified here: SYMPTOMS – EFFECTS – TREATMENT. Furthermore, in the samples analysed, the writers avoid evoking EU’s FUTURE RECOVERY, despite the presence of their thorough analysis of the EU measures taken to secure such. It can therefore be argued that, overall, The Economist puts forward a Eurosceptic or a heavily Eurocritical message on the issue.